2020
DOI: 10.31219/osf.io/bvph8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Dietary Trend in the World particularly in China and India

Abstract: Objective: Evaluate the trend of dietary convergence in the world. How specifically do Indian and Chinese diets have changed and middle-class consumption and evaluate their dietary trend? Methodology: The paper analyses the diet patter of India and China from 1990 to 2019. The paper is particularly keen to analyse the impact of income, urbanization and proportion of the young population on diet pattern. The data of food balance for these two countries is taken from FAOSTAT. To measure the income effect, the GN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
2
2
1
Order By: Relevance
“…This increase in India is mainly due to greater consumption of dairy products (+5% calorie share) and animal-based IPFs (+3.6%) but not meats. The increase from 235 to 368 animal kcal/day between 1990 and 2010 (+57%) was different from that previously reported, i.e., from approximately 150 to 220 between 1990 and 2010 (+47%) [49]. The difference between the two sources was mainly due to the data supplied by OECD.Stats used in this study [35], which reported a higher consumption of milk and added the consumption of fresh dairy products (mainly yogurts and other fermented milks) that was not mentioned in national Indian surveys.…”
Section: Metric 2: 85% Of Calories From Plantscontrasting
confidence: 93%
See 4 more Smart Citations
“…This increase in India is mainly due to greater consumption of dairy products (+5% calorie share) and animal-based IPFs (+3.6%) but not meats. The increase from 235 to 368 animal kcal/day between 1990 and 2010 (+57%) was different from that previously reported, i.e., from approximately 150 to 220 between 1990 and 2010 (+47%) [49]. The difference between the two sources was mainly due to the data supplied by OECD.Stats used in this study [35], which reported a higher consumption of milk and added the consumption of fresh dairy products (mainly yogurts and other fermented milks) that was not mentioned in national Indian surveys.…”
Section: Metric 2: 85% Of Calories From Plantscontrasting
confidence: 93%
“…Concerning calorie consumption by food group, our results in 2011-2012 are overall in good agreement with those reported by the National Sample Survey Organization (NSSO) of India in 2011-2012 [60], with 51.6 and 52.5% of calories obtained from cereals, 8.7 and 10.5% of calories obtained from IPFs, 0.8 and 1.0% of calories obtained from nuts and seeds, 3.1 and 4.0% of calories obtained from vegetables, and ≤ 1% of calories obtained from fish/seafood, eggs and meats. The decreases in cereal calorie intake (−13%) and the increase in fruit (+105%), vegetable (+47%) and milk (+91%) calorie intakes from 1990-2016 in our study were also previously observed (i.e., −9%, +112%, +86% and +70%, respectively), with no significant evolution in meat calorie intake in either analysis [49]. Finally, the increase in sugar consumption from 146 to 213 kcal/day between 1990 and 2018 agrees with that previously reported between 1990 and 2018 of 180 to 230 kcal/day, which also included other sweeteners [49].…”
Section: Data From Web Databases Versus Published Datasupporting
confidence: 87%
See 3 more Smart Citations